Coagulative function assessed preoperatively via the clot formation and lysis assay as a prognostic factor for blood loss in adolescents undergoing posterior spinal fusion for idiopathic scoliosis. Issue 11 (14th October 2019) - Fernandez, Allison M.; Neustadt, Jeffrey B.; Hahn, Gregory V.; Nguyen, Anh Thy H.; Amankwah, Ernest K.; Goldenberg, Neil A.
Abstract: Background: Posterior spinal fusion for adolescent idiopathic scoliosis is a complex surgery often associated with clinically significant blood loss leading to perioperative blood transfusion. Knowledge of risk factors for blood loss and transfusion stems mostly from retrospective studies. Aim: We sought to prospectively investigate putative prognostic factors for intraoperative blood loss and perioperative blood transfusion in adolescent idiopathic scoliosis patients undergoing posterior spine fusion, including clinical characteristics, surgical factors, and preoperative assessment of overall coagulative and fibrinolytic functions in plasma using the clot formation and lysis (CloFAL) assay. Methods: Following Internal Review Board approval, adolescents 10 to <21 years old with idiopathic scoliosis undergoing posterior spine fusion were enrolled preoperatively in a single‐institutional prospective cohort and biobanking study. Clinical data were collected on patient characteristics, surgical approach, perioperative management, intraoperative estimated blood loss, and blood transfusion through hospital discharge. Coagulative and fibrinolytic functions in plasma were measured on preoperative samples by CloFAL assay (Coagulation Index and modified Fibrinolytic Index). Univariate linear regression and multivariable linear regression were performed to identify predictors of weight‐indexed intraoperative estimated blood loss EBL (EBL/kg). Results: The final study population included 74 patients. Median age was 14.8 years (SD = 2.2). After adjustment for other putative prognostic factors via multivariable linear regression, coagulative function as determined preoperatively by CloFAL Coagulation Index was an independent predictor of intraoperative (EBL)/kg. Specifically, each 10% increase in CloFAL CI was associated with 3% decrease in the geometric mean of EBL/kg (OR 0.97, 95%CI 0.94‐0.99, P  = .01). Conclusion: In adolescents undergoing posterior spinal fusion for idiopathic scoliosis, increased coagulative function measured preoperatively using the CloFAL assay is independently associated with decreased intraoperative blood loss. Future studies should expand upon these investigations of plasma coagulative and fibrinolytic capacities in combination with clinical factors, to guide precise preventive strategies against blood loss and blood transfusion in this patient population.